The Integration of Test and Non-Test Assessment in Islamic Education toward Holistic Evaluation for Sustainable Learning - Diantoro Diantoro; Aji Joko Budi Pramono (The Future of Education Journal, 2026)
Islamic Religious Education (PAI) carries a sacred mission to develop students’ cognitive, affective, and psychomotor aspects in a balanced manner. However, in practice, learning evaluation in PAI remains dominated by test-based assessments that primarily measure the cognitive domain. This study is grounded in the increasing urgency to understand how the imbalance of evaluation instruments hinders the internalization of comprehensive Islamic character values (kaffah). This article aims to analyze the theological-pedagogical urgency, implementation mechanisms, and sociological-technical challenges of integrating test and non-test assessments in PAI in order to achieve holistic evaluation and sustainable learning. The study employed a Systematic Literature Review (SLR) method by adapting the PRISMA protocol to literature published between 2023 and 2025. Data were reduced and synthesized from various reputable journals. Of the 58 initial articles identified through scientific databases such as Google Scholar, Garuda, and Scopus, 15 final articles met the strict inclusion criteria for analysis. The findings indicate that the integration of test instruments (written and oral examinations) and non-test instruments (observation, self-assessment, and worship portfolios) simultaneously is capable of capturing both students’ theoretical and practical piety. This evaluation arrangement contributes directly to the long-term internalization of Islamic values. Although challenges remain, including teacher subjectivity, the halo effect, and administrative burdens, the digitalization of assessment instruments through application-based systems and the development of measurable and observable behavioral rubrics have emerged as strategic solutions to ensure evaluation objectivity in the modern era.